The great white bite: A critique of the Western Australian government's shark hazard mitigation drum line program. (December 2021) - Couper, Amy; Walters, Reece
The fatal shark bite of a scuba diver off the coast of Esperance in Western Australia in January 2020, followed in recent months by a further four fatalities in New South Wales and Queensland, has once again sparked debate about government policies to protect humans from potentially dangerous marine life. This debate is not new; during 2010–13 Western Australia experienced an unusually high level of human fatalities from shark bites. These events precipitated the introduction of the Western Australian Shark Hazard Mitigation Drum Line Program, a controversial and costly pre-emptive state government initiative that cost approximately $13.6 million for shark repellent responses, and the implementation of a Shark Response Unit. This research utilises official documents obtained under the Freedom of Information Act 1989 (Cth), together with interviews with relevant stakeholders, media reports, and public submissions to critically examine the political antecedents of a costly and flawed shark hazard mitigation program. It also provides lessons for how governments construct problems and manage marine environments and protected species. It concludes, utilising the theory of claims-making, that shark bite increases in Western Australia was a media constructed social problem, used to convince the government that a catch-and-kill policy of an internationally protected species was necessary to avert a perceived economic downturn in tourism revenue and to appease an invented public outcry.